(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Vitamin B12 named as Cobalamin a water-soluble vitamin plays significant role in several biological process such as DNA synthesis, Neurological function, and Optimal Haemopoiesis etc. The deficiency of vitamin B12 affects a number of processes, including the methylation of homocysteine, nucleoprotein, myelin production, DNA synthesis, lipid and glucose metabolism, and others. Vitamin B12 deficiency is a potential comorbidity that is often overlooked, but puts many diabetic patients at risk of developing particular complications. Various research showing an association between type 2 diabetes mellitus and a vitamin B12 deficiency. The purpose of the study is to find out the prevalence of vitamin B12 deficiency in Type 2 diabetic patients. 200 subjects of Type 2 diabetic patients were studied over a period of six months from August 2023 to February 2024 in the OPD of Kaya Chikitsha, Department of Ayurveda, IMS, Banaras Hindu University, Varanasi. Results: The present study summarizes that the prevalence of vitamin B12 deficiency in T2DM patients were 19% and 36% of respondents has borderline vitamin B12 level. The results also shows that the majority of male were having the deficiency of the vitamin B12 level as compare to the females. Study also shows the association of age and the vitamin B12 level (p<0.05).